2017
DOI: 10.1364/boe.8.005113
|View full text |Cite
|
Sign up to set email alerts
|

Real-time endoscopic optical properties imaging

Abstract: Abstract:With almost 50% of all surgeries in the U.S. being performed as minimally invasive procedures, there is a need to develop quantitative endoscopic imaging techniques to aid surgical guidance. Recent developments in widefield optical imaging make endoscopic implementations of real-time measurement possible. In this work, we introduce a proof-ofconcept endoscopic implementation of a functional widefield imaging technique called 3D single snapshot of optical properties (3D-SSOP) that provides quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…This could be done by incorporating SFDI systems into an open surgical procedure or by modifying endoscopy systems to achieve optical property measurements. Recent work has shown progress in implementing real‐time SFDI in a rigid endoscope and in a flexible endoscope . While these studies are only proofs of concept, they demonstrate feasibility of adapting SFDI for endoscopic assessment of optical properties and improved management of esophageal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be done by incorporating SFDI systems into an open surgical procedure or by modifying endoscopy systems to achieve optical property measurements. Recent work has shown progress in implementing real‐time SFDI in a rigid endoscope and in a flexible endoscope . While these studies are only proofs of concept, they demonstrate feasibility of adapting SFDI for endoscopic assessment of optical properties and improved management of esophageal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SFDI has been implemented to assess the presence of carcinomas in human colon tissue, proposing the applicability of SFDI in providing diagnostic information in GI tissue . Angelo et al has demonstrated proof‐of‐concept of real‐time SFDI endoscopy, but have yet to image human esophagus tissue . While NBI enhances superficial contrast by using lower wavelengths, SFDI can tune sampling depth, δ' eff , based on the projected spatial frequency, f x , and optical properties through the equation δˊeffbold=bold3μa()μabold-italic+bold-italicμbold-italicsbold-italic+2πbold-italicfbold-italicx2bold-italic−bold1.…”
Section: Introductionmentioning
confidence: 99%
“…15 Figure 4(e) (left, assembled and right, open) presents an endoscope configuration exploiting specifically real-time acquisition and processing advancements using single snapshot of optical properties (SSOP) developed at the University of Strasbourg, France. 16 These hardware advancements enable advanced intraoperative clinical acquisition in endoscopic applications where an open-field is not accessible. Finally, various other custom systems have been described by research groups around the world.…”
Section: Instrumentationmentioning
confidence: 99%
“…Multispatial frequency processing codes were developed to take into account this effect in cases where divergence is significant, such as within an endoscope. 16,40 Finally, many other sources of errors such as camera linearity, projection linearity, and source stability, as in any optical design should be taken into account, either by calibration or monitoring and/or appropriate analytic or empirical corrections. 41,42 One aspect that should not be neglected is the quality of the projection and acquisition, and the resulting demodulation as this will have a direct influence onto the precision and accuracy of the measurement.…”
Section: Key Considerationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Some medical fields in particular, such as surgery, are driving this need for realtime interpretable information content to aid decision-making in a time-constrained environment. [7][8][9][10][11][12] Several solutions have been investigated to fulfill this need, each with their pros and cons, ranging from raster scanning of microscopic information to wide-field acquisitions of diffused information. 13,14 For instance, fluorescence imaging to help surgeons visualizing structures of interest, such as lymph nodes, ureters, or micrometastasis, stands as an example where providing tissue-related information in real time plays a key role in clinical adoption.…”
Section: Introductionmentioning
confidence: 99%